Effects of alcohol solvents on formation of the hydrated silica gel - 이상은; 허소연; 고혜인; 이진숙; 권오훈; 홍창국; 김호준; 황종필; 안영수 (Journal of ceramic processing research, 2018)
Usually, when silica sol is prepared by adding inorganic acid to a diluted sodium silicate solution, a basic substance is addedto adjust the pH of the silica sol in order to occur the gelation reaction of the silica sol. However, in this study, it was confirmedthat the gelation of the silica sol could occur even when an alcohol is added instead of the basic substance. In order to examinethe mechanism of gelation that occurred when alcohol was added to the silica sol, different solvents (protic and aprotic) wereadded to the silica sol and the gelation time was measured. The results revealed that the gelation occurred due to the tendencyof the hydroxyl oxygen in the alcohol to bond to the hydroxyl hydrogen of the water molecules that had already formed ahydration shell around the silica particles. Therefore, it is presumed that the hydration shell was broken by the addition ofthe alcohol. This, in turn, led to the instantaneous polycondensation between the silica particles, which caused the gelation. KCI Citation Count: 2